The Impact of Maritime Diplomacy and Rules of Engagement Implementation on Maritime Security in the Malacca Strait - Wirawan, Bayu Indra; Suseto, Buddy; Saputra, Ditto R. (AGUSPATI Research Institute, 2025)
The Strait of Malacca is a vital strategic maritime route for global trade and holds significant economic value, yet it remains vulnerable to various maritime security threats such as piracy, smuggling, illegal fishing, and illegal migration. Although a trilateral cooperation between Indonesia, Malaysia, and Singapore has been established through the Malsindo Coordinated Patrol, its implementation still faces serious challenges. The main issues include the unresolved maritime boundary delimitation, differing perspectives on the involvement of external actors, disparities in capacity among the littoral states, and the absence of a jointly agreed standing Rules of Engagement (RoE). This study aims to: 1) Analyze the influence of maritime diplomacy and RoE on maritime security in the Strait of Malacca; 2) Examine the policies, strategies, and efforts to enhance maritime security in the Strait through maritime diplomacy and RoE; and 3) Assess the impact of the absence of a standing RoE on maritime security in the Strait of Malacca. The population of this study consists of 1,721 crew members of Indonesian warships under the First Fleet Command (who are involved in maritime security operations in the Strait of Malacca. The sample was determined using Slovin's formula with a 10% precision level, resulting in a total of 95 respondents. This research employs a mixed-method approach. The findings of the study reveal that: 1) Maritime diplomacy and RoE implementation have a significant effect on improving maritime security in the Strait of Malacca, both partially and simultaneously; 2) The general policy formulated in this study emphasizes the enhancement of maritime security in the Strait through maritime diplomacy and RoE implementation. This policy is elaborated into three main strategies: First, strengthening the trilateral cooperation forum among Indonesia, Malaysia, and Singapore to align national interests in securing global shipping routes; Second, formulating a standing RoE that is adaptive to regional dynamics and global economic interests; and Third, increasing human resource capacity and maritime technology in less developed countries, supported by advancements in science and international cooperation.